In Arabidopsis thaliana, the invertase inhibitors AtC/VIF1 and 2 exhibit distinct target enzyme specificities and expression profiles - Link, Manuela; Rausch, Thomas; Greiner, Steffen (FEBS letters, 2004)
Plant cell wall (CWI) and vacuolar invertases (VI) play important roles in carbohydrate metabolism, stress responses and sugar signaling. Addressing the regulation of invertase activities by inhibitor proteins (C/VIF, ell wall/acuolar nhibitor of ructosidase), we have identified two C/VIFs from Arabidopsis thaliana. AtC/VIF1 showed specific inhibition of VI activity, whereas AtC/VIF2 inhibited both, CWI and VI. Expression analysis revealed that expression of AtC/VIF1 was restricted to specific organs, AtC/VIF2, however, was weakly expressed throughout plant development. Promoter::GUS transformants confirmed pronounced differences of tissue/cell type-specific expression between both isoforms. Growth of an AtC/VIF1 T-DNA KO mutant was unaffected, but VI activity and hexose content were slightly increased.